'I Can' vs. 'I Want': What's Missing from Gallagher's Picture of Non-reductive Cognitive Science. Issue 2 (3rd April 2018) - Barrett, Nathaniel F.; García-Valdecasas, Miguel; Sánchez-Cañizares, Javier
Abstract: We support the development of non-reductive cognitive science and the naturalization of phenomenology for this purpose, and we agree that the 'relational turn' defended by Gallagher is a necessary step in this direction. However, we believe that certain aspects of his relational concept of nature need clarification. In particular, Gallagher does not say whether or how teleology, affect, and other value-related properties of life and mind can be naturalized within this framework. In this paper, we argue that (1) given the phenomenological standards recognized by Gallagher, his commitment to a naturalized phenomenology should entail a commitment to a naturalized concept of value; and (2) the kind of 'relational nature' described by Gallagher in his paper is insufficient for this purpose